Investigating multidrug efflux pumps associated with fatty acid salt resistance in Escherichia coli - Yamasaki, Seiji; Yoneda, Tomohiro; Ikawa, Sota; Hayashi-Nishino, Mitsuko; Nishino, Kunihiko (Frontiers in Microbiology, 2023)
Fatty acids salts exert bactericidal and bacteriostatic effects that inhibit bacterial growth and survival. However, bacteria can overcome these effects and adapt to their environment. Bacterial efflux systems are associated with resistance to different toxic compounds. Here, several bacterial efflux systems were examined to determine their influence on fatty acid salt resistance in Escherichia coli. Both acrAB and tolC E. coli deletion strains were susceptible to fatty acid salts, while plasmids carrying acrAB, acrEF, mdtABC, or emrAB conferred drug resistance to the ΔacrAB mutant, which indicated complementary roles for these multidrug efflux pumps. Our data exemplify the importance of bacterial efflux systems in E. coli resistance to fatty acid salts.